Diagnóstico de enfermagem em clientes vivenciando estressores pré-cirúrgicos - Sousa, Santana de Maria Alves de (1997)
Nursing’s diagnosis in patients under pre-surgical stress, is a exploratory and descriptive study aiming at an avaliation of patients under pre-surgical stress, with the purpose of identifying diagnosis resulting from this experience. The sample here studied is of 20 male and female patients hospitalized in clinicai surgery at Hospital Universitario-UFMA in São Luís-Maranhão-Brazil in the months of May and June 1996, to undergo an elective abdominal surgery. The data was collected by the author through interviews using as a guide the Model of the Systems of NEUMAN, thaí focalizes the patient subject to the impact of environment stress and his/her reactions. After collection the data this was transcoded from spoken language and observation of patients, grouped and classified in accordance to the thematic expressions that indicated the category of the stress as stated by Taxonomy I NANDA . Following, they were validated by the Scale of Measuration of the Diagnosis Procedure ,as a result, for this study, 14 nursing diagnosis were identified aíl related to pre-surgical stress. From these, 11 were validated in accordance to the criterion selected by the author, which are: anxiety, found in 100% of the samples, fear 60%, risk of infection 40%, constipation 30%, sleep disturbance 15%, maintenance of an altered in health State 15%, risk of prejudice physical mobility 10%, refusal 5%, defensive strategy in resoiution 5%, risk of ineficiency in breathing standart 5%, excess in the volume of liquid 5%. The discussion was around the definer characteristics pointed out in each diagnosis, and at the light of the literature on each subject.